Patient Tobacco Use, Quit Attempts, and Perceptions of Healthcare Provider Practices in a Safety-Net Healthcare System - Moody-Thomas, Sarah (the Academic Division of Ochsner Clinic Foundation, 2013)
BACKGROUND: Although smoking rates in the United States (US) are high, healthcare systems and clinicians can increase cessation rates through application of the US Public Health Service tobacco treatment guideline (2000, 2008). In primary care settings, however, guideline implementation remains low. This report presents the results from an assessment of patient tobacco use, quit attempts, and perceptions of provider treatment before (2004) and after (2010) guideline implementation. METHODS: By use of a systems approach, the Louisiana Tobacco Control Initiative integrated evidence-based treatment of tobacco use into patient care practices in Louisiana's public hospital system. This prospective study, designed to collect data at 2 time points for the purpose of evaluating the effect of the 5A protocol (ask, advise, assess, assist, and arrange), included 571 and 889 adult patients selected from primary care clinics in 2004 and 2010, respectively. Chi-square analyses determined differences between survey administrations, along with direct standardization of weighted rates to control for confounding factors. RESULTS: Patient reports indicated that provider adherence to the 5A clinical protocol increased from 2004 to 2010. Significant (P<0.001) improvements were observed for the assess (39% vs 72%), assist (24% vs 76%), and arrange (8% vs 31%) treatment variables. Patient-reported quit attempts increased, along with awareness of cessation services (from 19% to 70%, P<0.001), while use of cessation medications decreased (from 23% to 5%, P<0.002). CONCLUSION: Following implementation of the guideline, significant improvements were noted in patient reports of provider treatment and awareness of cessation services.